Enhancing methane production of corn stover through a novel way: Sequent pretreatment of potassium hydroxide and steam explosion. (April 2015) - Li, Jianghao; Zhang, Ruihong; Siddhu, Muhammad Abdul Hanan; He, Yanfeng; Wang, Wen; Li, Yeqing; Chen, Chang; Liu, Guangqing
Highlights: Strength of pretreatment to CS ascended in the following order: KOH, SE, and SPPE. SPPE was firstly reported to effectively destroy lignocellulosic structure of CS. Methane production of CS was significantly enhanced by 80.0% after SPPE. Abstract: Getting over recalcitrance of lignocellulose is effective way to fuel production from lignocellulosic biomass. In current work, different pretreatments were applied to enhance the digestibility of corn stover (CS). Results showed that steam explosion (SE)-treated CS produced maximal methane yield (223.2 mL/gvs ) at 1.2 MPa for 10 min, which was 55.2% more than untreated (143.8 mL/gvs ). Whereas 1.5% KOH-treated CS produced maximum methane yield of 208.6 mL/gvs, and significantly ( α < 0.05) improved 45.1% with respect to untreated. Sequent pretreatment of potassium hydroxide and steam explosion (SPPE) (1.5% KOH-1.2 MPa, 10 min) achieved a very significant ( α < 0.01) improvement (80.0%) of methane yield (258.8 mL/gvs ) compared with untreated CS. Methane production could be well explained by the first-order and modified Gompertz models. Besides, SEM, FTIR, and XRD analyses validated structural changes of CS after SPPE. SPPE might be a promising method to pretreat CS in the future AD industry.